Model dan Strategi dalam Menghadapi Perubahan di SMA Muhammadiyah 4 Kota Bandung - Zulfa Fadilah; Wahyu Hidayat (Jurnal Administrasi Pendidikan Islam, 2023)
This study aims to find out the models and strategies used in dealing with changes at SMA Muhammadiyah 4 Bandung City. This research method uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The subject of the study is the Principal. The location of this study is SMA Muhammadiyah 4 Bandung City. The results of this study show that: 1) In one period of principal leadership, there were several changes. These changes consist of changes in facilities and infrastructure, changes in curriculum, changes in the number of students and changes in the ethics of educators and education personnel. 2) The model used by SMA Muhammadiyah 4 Bandung City in facing changes is the Tyagi model. 3) The strategy used by SMA Muhammadiyah 4 Bandung City in facing change is First, creating a team atmosphere that is not afraid of change. Second, discover what kind of dissatisfaction caused the employees to want to change. Third, the principal indicated which way the change would lead.